Possible interactions between selected food processing and medications - Poli, Giuseppe; Bologna, Ettore; Saguy, I. Sam (Frontiers in Nutrition, 2024)
The impact of food processing on drug absorption, metabolism, and subsequent pharmacological activity is a pressing yet insufficiently explored area of research. Overlooking food-processing-drug interactions can significantly disrupt optimal clinical patient management. The challenges extend beyond merely considering the type and timing of food ingestion as to drug uptake; the specific food processing methods applied play a pivotal role.This study delves into both selected thermal and non-thermal food processing techniques, investigating their potential interference with the established pharmacokinetics of medications.Within the realm of thermal processing, conventional methods like deep fat frying, grilling, or barbecuing not only reduce the enteric absorption of drugs but also may give rise to sideproducts such as acrylamide, aldehydes, oxysterols, and oxyphytosterols. When produced in elevated quantities, these compounds exhibit enterotoxic and pro-inflammatory effects, potentially impacting the metabolism of various medications. Of note, a variety of thermal processing is frequently adopted during the preparation of diverse traditional herbal medicines.Conversely, circumventing high heat through innovative approaches (e.g., high-pressure processing, pulsed electric fields, plasma technology), opens new avenues to improve food quality, efficiency, bioavailability, and sustainability. However, it is crucial to exercise caution to prevent the excessive uptake of active compounds in specific patient categories.The potential interactions between food processing methods and their consequences, whether beneficial or adverse, on drug interactions can pose health hazards in certain cases.Recognizing this knowledge gap underscores the urgency for intensified and targeted scientific inquiry into the multitude of conceivable interactions among food composition, processing methods, and pharmaceutical agents. A thorough investigation into the underlying mechanisms is imperative. The complexity of this field requires substantial scrutiny and collaborative efforts across diverse domains, including medicine, pharmacology, nutrition, food science, food technology, and food engineering.